2020
DOI: 10.21873/invivo.12199
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes of Pathological T1 Lower Rectal Cancer Patients With or Without Preoperative Chemoradiotherapy

Abstract: Background/Aim: It remains unclear whether rectal cancers down-staged by preoperative chemoradiotherapy (CRT) have similar prognoses to those of the same stage without preoperative CRT. We compared prognoses of pT1 rectal cancer patients stratified by preoperative CRT. Patients and Methods: We retrieved data of patients with pathological T1 rectal cancer between 2003 and 2020. Patients were divided into the "ypT1 group" who received preoperative CRT following surgery and the "pT1 group" who underwent surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the current study, we have performed a similar analysis using the data from >3,000 ypT1 or pT1 patients available in the SEER database and showed that (i) there was no difference in OS between ypT1 and pT1 rectal cancer patients and (ii) preoperative therapy was not a prognostic factor of CSS or OS. Importantly, these results are consistent with our previous observations in a single-center cohort of 86 patients [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, we have performed a similar analysis using the data from >3,000 ypT1 or pT1 patients available in the SEER database and showed that (i) there was no difference in OS between ypT1 and pT1 rectal cancer patients and (ii) preoperative therapy was not a prognostic factor of CSS or OS. Importantly, these results are consistent with our previous observations in a single-center cohort of 86 patients [14].…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported on the prognosis of 18 patients with ypT1N0 stage lower rectal cancer in comparison with 68 patients with pT1N0 stage cancer who did not undergo preoperative CRT in our hospital and showed that there was no difference in RFS between ypT1 and pT1 patients; preoperative CRT was not a prognostic factor [14]. In the current study, we have performed a similar analysis using the data from >3,000 ypT1 or pT1 patients available in the SEER database and showed that (i) there was no difference in OS between ypT1 and pT1 rectal cancer patients and (ii) preoperative therapy was not a prognostic factor of CSS or OS.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Taira, T. et al performed preoperative rectal ultrasound examination in 52 patients with rectal cancer and compared the ultrasound examination results with postoperative pathological results. The objective of this study was to further evaluate the accuracy and influencing factors of intravascular ultrasound in preoperative diagnosis of rectal cancer staging and to study the relationship between preoperative intravascular ultrasound staging and preoperative serum carcinoembryonic antigen (CEA) value [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%